THE IMPORTANCE OF TEACHING MATHEMATICS IN STUDENT LIFE - Turapov Sohiba Jumanazarovna (Galaxy International Interdisciplinary Research Journal, 2021)
Experts say that a student who masters mathematics well will have a high level of analytical and logical thinking. It develops the ability to make quick decisions, discuss and negotiate, and do things step by step, not only in solving examples and problems, but also in different situations in life.